Ruthenium‐Catalyzed Hydrocarboxylation of Internal Alkynes. Issue 8 (12th February 2016) - Jeschke, Janine; Engelhardt, Tony B.; Lang, Heinrich
Abstract: The application of the highly efficient ruthenium catalyst [Ru(CO)2 {P( p ‐CF3 –C6 H4 )3 }2 (O2 CPh)2 ] (1 ) in the selective syn ‐addition of carboxylic acids to internal alkynes, yielding valuable trisubstituted enol esters with ( E )‐configuration, is described. All reactions feature excellent stereoselectivities and good regioselectivities. The regioselectivity is dictated by electronic and steric aspects of the alkyne substituents and the acidity of the carboxylic acid. The catalytic activity can be significantly increased by the addition of catalytic amounts of B(C6 F5 )3 . Relative to known catalysts for the synthesis of ( E )‐enol esters, this methodology offers improved selectivity and requires lower catalyst loadings. Moreover, a broad range of alkynes and carboxylic acids can be successfully converted to their corresponding ( E )‐enol esters in high yields. Abstract : The metal complex [Ru(CO)2 {P( p ‐CF3 –C6 H4 )3 }2 (O2 CPh)2 ] is demonstrated to be a highly efficient catalyst in the challenging hydrocarboxylation of internal alkynes. Using this catalyst, a diverse array of substrates were selectively converted to their trisubstituted ( E )‐enol esters.